Low cost porous alumina with tailored microstructure and thermal conductivity prepared using rice husk and sucrose - Mohanta K.; Kumar A.; Parkash O.; Kumar D. (My University, 2025)
This study demonstrates a cost-effective way to fabricate porous ceramics with tailored porosity and pore microstructure using 5-40 wt% rice husk (RH) in <75 μm, 75-180 μm, 180-355 μm, 355-420 μm, and 420-600 μm size, as pore former. Sucrose, used as binder, also acted as a pore former. Porous alumina compacts with 20%-66% volume fraction porosity and 50-516 μm pore size (length) were successfully fabricated. Microstructure of samples reveal randomly oriented elongated coarse pores and fine pores (avg. size 4 μm), created during burnout of RH and sucrose, respectively. Samples with isolated and/or interconnected pores were fabricated using this process. Thermal conductivity of the samples prepared was measured using Transient Plane Source (TPS) technique. Thermal conductivity ranges from 1.2 to 24 W/mK. Experimental results agree closely with predictions made based on Effective Medium Theory (EMT) for a two-phase system. © 2014 The American Ceramic Society.